Inventario de Gases de Efecto Invernadero del Centro de Servicio de Recursos Geotérmicos, Guanacaste - Vallejos-Esquivel, Luis Alonso (Instituto Tecnológico de Costa Rica, 2016)
Global warming is an effect caused by the increasing of concentrations of greenhouse gases in the Earth's atmosphere. Costa Rica is an example to the world on environmental protection, this is why the country was proposed it as a goal to reduce in 50% the emissions of greenhouse gases in comparison of 2012. One of the main strengths of the country is having an energy matrix with 97% renewable sources, such is the case of the production of geothermal energy in the province of Guanacaste. The Centro de Servicios de Recursos Geotérmicos is responsible for the exploration, development and exploitation of geothermal fields. This paper presents the first step to achieve zero carbon emissions by quantifying the inventory of greenhouse gases under the INTE-ISO14064-1 standard, resulting in the total amount of carbon dioxide released into the Earth's atmosphere for the year 2014 was 6 115,31 t CO2e, where diesel consumption was the main source providing a 90,78% of the amount of emissions inventory.
Proyecto de Graduación (Licenciatura en Ingeniería en Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Química, 2016.
Keywords: Calentamiento global; Efecto invernadero; Inventario de gases de efecto; Dióxido de carbono; Energía geotérmica